Kinerja dan Perspektif Usahatani Konservasi Alley Cropping di Indonesia (Forum Penelitian Agro Ekonomi, 2016)
Alley cropping as a soil conservation technology owning certain advantages over terracing, particularly in that : a) costs are lower, b) soil productivity can be maintained, and c) it may be applied on all soil conditions. A disadvantage of alley cropping relates to the time taken for soil erosion control to become effective. However, over the longer time period, soil conversation control through alley cropping technology is more economical than that for terracing. The reviewed studies indicate that flemingia congesta is the most effective soil erosion controlling leguminous shrub,of those studied. Alley cropping is effective in maintaining land productivity. The synergic effect of soil productivity increase and soil erosion rate reduction. In some research,alley cropping systems have been shown to significantaly reduce farming costs per unit output,due to a decrease in manday (labour) use and other input reductions. In implementing alley cropping, land-holding status is one determining fector in farmers' willingness to apply the technology. That is why efforts to disseminate soil cinversation technology have often used some incentive in terms of land ownership rights for farmers. It is worthwhile to develop these incentives further, so that there is a legal certainty on cultivated land. Although alley cropping technology has currently been applied and adopted by farmers to a limited degree, there are still four main assues obstructing farmers' adoption of the tecnolog: a) small scale land-holding; b) limited capital ; c) production input availability; and d) lack of technology information